Endoscopistsʼ diagnostic accuracy in detecting upper gastrointestinal neoplasia in the framework of artificial intelligence studies - Frazzoni, Leonardo; Arribas, Julia; Antonelli, Giulio; Libanio, Diogo; Ebigbo, Alanna; van der Sommen, Fons; de Groof, Albert Jeroen; Fukuda, Hiromu; Ohmori, Masayasu; Ishihara, Ryu; Wu, Lianlian; Yu, Honggang; Mori, Yuichi; Repici, Alessandro; Bergman, Jacques J. G. H. M.; Sharma, Prateek; Messmann, Helmut; Hassan, Cesare; Fuccio, Lorenzo; Dinis-Ribeiro, Mário (Endoscopy, 2021)
Background Estimates on miss rates for upper gastrointestinal neoplasia (UGIN) rely on registry data or old studies. Quality assurance programs for upper GI endoscopy are not fully established owing to the lack of infrastructure to measure endoscopists’ competence. We aimed to assess endoscopists’ accuracy for the recognition of UGIN exploiting the framework of artificial intelligence (AI) validation studies.Methods Literature searches of databases (PubMed/MEDLINE, EMBASE, Scopus) up to August 2020 were performed to identify articles evaluating the accuracy of individual endoscopists for the recognition of UGIN within studies validating AI against a histologically verified expert-annotated ground-truth. The main outcomes were endoscopists’ pooled sensitivity, specificity, positive and negative predictive value (PPV/NPV), and area under the curve (AUC) for all UGIN, for esophageal squamous cell neoplasia (ESCN), Barrett esophagus-related neoplasia (BERN), and gastric adenocarcinoma (GAC).Results Seven studies (2 ESCN, 3 BERN, 1 GAC, 1 UGIN overall) with 122 endoscopists were included. The pooled endoscopists’ sensitivity and specificity for UGIN were 82 % (95 % confidence interval [CI] 80 %–84 %) and 79 % (95 %CI 76 %–81 %), respectively. Endoscopists’ accuracy was higher for GAC detection (AUC 0.95 [95 %CI 0.93–0.98]) than for ESCN (AUC 0.90 [95 %CI 0.88–0.92]) and BERN detection (AUC 0.86 [95 %CI 0.84–0.88]). Sensitivity was higher for Eastern vs. Western endoscopists (87 % [95 %CI 84 %–89 %] vs. 75 % [95 %CI 72 %–78 %]), and for expert vs. non-expert endoscopists (85 % [95 %CI 83 %–87 %] vs. 71 % [95 %CI 67 %–75 %]).Conclusion We show suboptimal accuracy of endoscopists for the recognition of UGIN even within a framework that included a higher prevalence and disease awareness. Future AI validation studies represent a framework to assess endoscopist competence.